2009
DOI: 10.1002/jgm.1332
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type 5 with modified hexons induces robust transgene‐specific immune responses in mice with pre‐existing immunity against adenovirus type 5

Abstract: These data demonstrate that Ad5 vector with hexon modification reduce their sensitivity to pre-existing anti-Ad immunity and improve their clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 49 publications
3
46
1
Order By: Relevance
“…This conclusion was corroborated by the fact that when anti-P. yoelii CS antibody was used to neutralize rAd in vitro, it neutralized equally both HVR1-and HVR5-modified rAds, suggesting that an epitope present in HVR5 can also be a target of neutralizing antibody, albeit to a lesser degree. The observation of HVR5 being the possible target of neutralizing antibody in addition to HVR1 is not contradictory to the study by Roberts et al, which reported that replacement of all HVRs with those of Ad48 was necessary to completely circumvent preexisting immunity to Ad5 (20), or to the study by Abe et al, which showed that HVR5 modification could also circumvent preexisting anti-Ad5 immunity, although they never compared the effect of HVR5 modification with that of HVR1 modification (29). In our study, the percentage of neutralizing antibody against HVR1 within all neutralizing antibodies seems to differ among human sera, and this variation could arise from the difference in immunogenicity of HVRs among individuals.…”
Section: Figurementioning
confidence: 62%
“…This conclusion was corroborated by the fact that when anti-P. yoelii CS antibody was used to neutralize rAd in vitro, it neutralized equally both HVR1-and HVR5-modified rAds, suggesting that an epitope present in HVR5 can also be a target of neutralizing antibody, albeit to a lesser degree. The observation of HVR5 being the possible target of neutralizing antibody in addition to HVR1 is not contradictory to the study by Roberts et al, which reported that replacement of all HVRs with those of Ad48 was necessary to completely circumvent preexisting immunity to Ad5 (20), or to the study by Abe et al, which showed that HVR5 modification could also circumvent preexisting anti-Ad5 immunity, although they never compared the effect of HVR5 modification with that of HVR1 modification (29). In our study, the percentage of neutralizing antibody against HVR1 within all neutralizing antibodies seems to differ among human sera, and this variation could arise from the difference in immunogenicity of HVRs among individuals.…”
Section: Figurementioning
confidence: 62%
“…However, the relative importances of the seven individual HVRs as NAb epitopes remain incompletely understood, and recent studies have suggested that Ad5 NAb responses may actually be focused primarily on one specific HVR, such as HVR1 or HVR5 (1,15). In this study, we characterized the contribution of individual hexon HVRs as Ad5 NAb epitopes.…”
mentioning
confidence: 97%
“…We previously reported that replacing all seven hexon HVRs in Ad5 with those from a rare human adenovirus serotype, Ad48, resulted in a chimeric vector, Ad5HVR48 (1)(2)(3)(4)(5)(6)(7), that evaded the majority of preexisting Ad5 immunity in preclinical studies in mice and rhesus monkeys (13). However, the relative importances of the seven individual HVRs as NAb epitopes remain incompletely understood, and recent studies have suggested that Ad5 NAb responses may actually be focused primarily on one specific HVR, such as HVR1 or HVR5 (1,15).…”
mentioning
confidence: 99%
“…Several approaches have therefore been developed to circumvent pre-existing anti-Ad5 immunity and/or to facilitate the induction of potent adaptive immune responses by Ad-based vaccines in general. These approaches include the use of novel Ad5-based platforms (15,16), modification of Ad5 structure (17), and the development of alternative serotype (human-or chimpanzeederived) adenovirus-based vectors (18).…”
mentioning
confidence: 99%